Democracy and authoritarianism in South Asia : a comparative and historical perspective - "Jalal, Ayesha" (New Delhi, 1995)
This volume has takes shape during mu sojourns at various academic institutions int the \united States since 1987, all of which share the credits in different measure.Intellectually it forms a bridge between my earlier monographs and current research on multiple identities and theories of sovereignty in South Asia. The inspiration for it was provided by my students at Wisconsin- Madison, Tufts and, above all, above all, Columbia and it is largely for them that I decided to undertake a work of this level of generality and, hopefully, accessibility.